2018
DOI: 10.2106/jbjs.rvw.17.00072
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes After Limb-Sparing Resection and Reconstruction for Pelvic Sarcoma

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…With the depressing performance of systematic therapy in pelvic sarcoma, it seems that the only available option for now is to improve our surgery to get better local control. However, pelvic tumor surgeries are always challenging and with high complication rates (16,17). Thus, proper preoperative planning is of vital importance.…”
Section: Discussionmentioning
confidence: 99%
“…With the depressing performance of systematic therapy in pelvic sarcoma, it seems that the only available option for now is to improve our surgery to get better local control. However, pelvic tumor surgeries are always challenging and with high complication rates (16,17). Thus, proper preoperative planning is of vital importance.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al8 found that the MSTS was the most frequently used measure and that the TESS was presented only once for pelvic sarcoma patients. Some studies have used both the older and newer versions of the MSTS questionnaires in the same study 18,41.…”
Section: Discussionmentioning
confidence: 99%
“…Groundland et al7 investigated pediatric patients. Wilson et al8 studied pelvic sarcoma patients, and Winnette et al9 investigated all patients with STS, including abdominal sarcomas. Thus, no systematic literature review has previously focused specifically on measurement of FO after surgical treatment of adult lower-extremity STS patients.…”
mentioning
confidence: 99%
“…5 A systematic review of the surgical outcomes of patients with pelvic sarcoma reported a mean nononcologic complication rate of 49%. 6 Moreover, reconstruction methods after surgical resection such as hip transposition, arthrodesis, prosthesis, allograft, ipsilateral proximal femur, and extracorporeal irradiated autograft reportedly are associated with dysfunction. 5,[7][8][9][10][11][12][13] Some patients have refused to undergo surgical resection because of the high complication rate, the possibility of postoperative dysfunction, and limited improvement in prognosis.…”
Section: Introductionmentioning
confidence: 99%